Pengaruh Persentase RDF terhadap Cold Gas Efficiency pada Co-Gasifikasi Batubara Dual Reactor Fluidized Bed - Darma, I Wayan Arya; Winaya, I Nyoman Suprapta; Pratama, Yuda I Putu Angga; Irfan, Yunizill (CV. IRA PUBLISHING, 2026)
Refuse-derived fuel (RDF) can be used as an alternative fuel through gasification to produce syngas. Co-gasification, which involves blending two or more fuels, has been shown to enhance system performance compared to single-fuel gasification. The addition of RDF with high volatile matter content can improve fuel reactivity and reduce slagging. This study aims to analyze the effect of RDF percentage on coal co-gasification performance in a Dual Reactor Fluidized Bed (DRFB) system. The study demonstrates the relationship between increasing RDF percentage and the enhancement of combustible gas components (CO and H2) and Cold Gas Efficiency. Experiments were conducted with RDF variations of 0%, 5%, 10%, 15%, and 20% of the total fuel mass (0.6 kg). Results show that increasing RDF raises CO from 3.47% to 4.13% and H2 from 2.36% to 2.85%, while CH4 remains relatively constant, leading to an increase in syngas heating value from 2.68 MJ/m3 to 3.07 MJ/m3. Cold Gas Efficiency also increases from 36.21% to 45.04%. Despite a decrease in the heating value of the fuel mixture, enhanced reactivity and improved gasification reactions contribute to better syngas quality and overall system performance.